Cumulative, high-stress calls impacting adverse events among law enforcement and the public - Katelyn K. Jetelina; Alaina M. Beauchamp; Jennifer M. Reingle Gonzalez; Rebecca J. Molsberry; Stephen A. Bishopp; Simon Craddock Lee (BMC, 2020)
Abstract Background The unpredictable, and sometimes dangerous, nature of the occupation exposes officers to both acute and chronic stress over law enforcement officers' (LEO)  tenure. The purpose of this study is two-fold: 1) Describe multi-level characteristics that define high-stress calls for service for LEO; and 2) Characterize factors that impact cumulative stress over the course of a LEO's shift. Methods Qualitative data were collected from 28 LEOs at three law enforcement agencies in the Dallas-Fort Worth areas from April 2019 to February 2020. Focus group data were iteratively coded by four coders using inductive and deductive thematic identification. Results Five multi-level factors influenced officer stress: 1) officer characteristics (e.g. military experience; gender); 2) civilian behavior (e.g. resistance, displaying a weapon); 3) supervisor factors (micromanagement); 4) environmental factors (e.g. time of year); and, 5) situational factors (e.g. audience present; complexity of calls). Four themes that characterized cumulative stress: 1) cyclical risk; 2) accelerators; 3) decelerators; and 4) experience of an adverse event. Conclusions LEOs become susceptible to adverse events (e.g. injury, excessive use of force) after repeated exposure to high-stress calls for service. Ongoing exposures to stress continue to occur throughout the shift. Our long-term goal is to interrupt this repetitive, cumulative process by restricting the number of consecutive high-risk, high-intensity calls an officer is permitted to respond to.